Genome sequence of the halotolerant bacterium Corynebacterium halotolerans type strain YIM 70093T (= DSM 44683T). Issue 2 (September 2012) - Rückert, Christian; Albersmeier, Andreas; Al-Dilaimi, Arwa; Niehaus, Karsten; Szczepanowski, Rafael; Kalinowski, Jörn
Abstract Corynebacterium halotolerans Chenet al. 2004 is a member of the genusCorynebacterium which contains Gram-positive bacteria with a high G+C content.C. halotolerans, isolated from a saline soil, belongs to the non-lipophilic, non-pathogenic corynebacteria. It displays a high tolerance to salts (up to 25%) and is related to the pathogenic corynebacteriaC. freneyi andC. xerosis . As this is a type strain in a subgroup ofCorynebacterium without complete genome sequences, this project describing the 3.14 Mbp long chromosome and the 86.2 kbp plasmid pCha1 with their 2, 865 protein-coding and 65 RNA genes will aid theG enomic E ncyclopedia of B acteria and A rchaea project.